Development and characterization of porous functionalized collagen scaffolds for delivery of FGF-2 - Pokholenko, Ia.O.; Chetyrkina, M.D.; Dubey, L.V.; Dubey, I.Ya.; Moshynets, O.V.; Sheludko, E.V.; Shpylova, S.P.; Degtiarova, M.I.; Kordium, V.A. (Вiopolymers and Cell, 2014)
Aim. To develop the porous functionalized collagen scaffold for the delivery of FGF-2 and studying its properties in vitro and in vivo. Methods. Porous collagen scaffolds were prepared by freeze- drying collagen I solutions containing the polymer developed on the basis of cross-linked modified heparin. The scaffolds have been analyzed by SEM, AFM and SCLM. The angiogenic activity of these scaffolds loaded with FGF-2 was tested in a CAM assay. Results. The data obtained by SEM and SCLM analysis revealed that the scaffold mainly has a layered structure with pores forming a connection between the layers. The average pore size of the scaffolds varied from 76 to 150 µm. Scaffolds containing the polymer were able to incorporate human FGF-2. Proposed compositions promoted angiogenesis in CAM assay. Conclusions. The developed porous functionalized collagen scaffold incorporating FGF-2 can be used as a vehicle for the sustained delivery of the growth factor both in vitro and in vivo. Мета. Розробка пористих функціоналізованих колагенових скафолдів для доставки FGF-2, а також вивчення їхніх властивостей in vitro та in vivo. Методи. Пористі колагенові скафолди одержано методом ліофільного сублімаційного висушування розчину колагену типу І, який містить створений полімер на основі моди- фікованого зшитого гепарину. Скафолди аналізували методами СЕМ, АСМ і ЛСКМ. Ангіогенні властивості колагенових скафолдів, які містять FGF-2, вивчали на моделі хоріон-алантоїсної мембрани ембріона курчати. Результати. Дані, отримані методами СЕМ і ЛСКМ, свідчать про те, що одержаний скафолд має перважно шарувату структуру з порами, які зўєднують різні шри. Середній розмір пор варіює від 76 до 150 мкм. Скафолди, до складу яких входить створений полімер, здатні адсорбувати рекомбінантний FGF-2 людини. Запропоновані композиції стимулюють ангіогенез на моделі хоріон-алантоїсної мембрани ембріона курчати. Висновки. Розроблені пористі функціоналізовані колагенові скафолди, які містять FGF-2, можна використовувати як засіб для доставки даного ростового фактора, що забезпечує його тривале вивільнення як in vitro, так in vivo. Цель. Разработка пористых функционализированных коллагеновых скаффолдов для доставки FGF-2 и изучение их свойств in vitro и in vivo. Методы. Пористые коллагеновые скаффолды получены методом лиофильной сублимационной сушки раствора коллагена типа I, содержащего созданный полимер на основе модифицированного сшитого гепарина. Скаффолды анализировали методами СЭМ, АСМ и ЛСКМ. Ангиогенные свойства разработанных коллагеновых скаффолдов, содержащих FGF-2, изучали на модели хорион-аллантоисной мембраны куриного эмбриона. Результаты. Данные, полученные методами СЭМ и ЛСКМ, свидетельствуют о том, что созданный скаффолд в основном имеет слоистую структуру с порами, соединяющими разные слои. Средний размер пор варьирует от 76 до 150 мкм. Скаффолды, содержащие полученный полимер, способны адсорбировать рекомбинантный FGF-2 человека. Предложенные композиции стимулируют ангиогенез на модели хорион-аллантоисной мембраны куриного эмбриона. Выводы. Разработанные пористые функционализированные коллагеновые скаффолды, содержащие FGF-2, можно использовать как средство для доставки данного ростового фактора, обеспечивающее его длительное высвобождение, как in vitro, так in vivo.